F182. Intraoperative local field potential recordings from deep brain stimulation electrodes help predict efficacy of subthalamic nucleus stimulation in patients with Parkinson's disease. (May 2018) - Liu, Min-Yin; Chen, Chiung Chu; Chan, Hsiao-Lung; Liu, Wey-Yil; Tu, Po-Hsun; Brown, Peter; Lu, Chin-Song; Lee, Shih-Tseng
Abstract : Introduction: Subthalamic nucleus (STN) deep brain stimulation (DBS) is an effective treatment for advanced Parkinson's disease (PD). Two electrophysiological techniques aid identification of the optimal target. One is to record neuronal activity with microelectrodes (MER). The other is to record the local field potential (LFP) from the DBS electrode used for chronic stimulation. The relative predictive value of the two techniques is yet to be established. Methods: We combined MER and LFP recordings during STN electrode implantation in 18 PD patients. The LFP was recorded from the DBS electrode as it descended in 1 mm steps through the STN. The upper border of the STN identified by MER and the depth of the highest beta peak (HBP) recorded by the DBS electrode were correlated with the depth of chronic stimulation and with stimulation efficacy determined later. Results: The HBP in the LFP recorded with the DBS electrode predicted the optimal contact for chronic stimulation slightly better than the upper border of the STN identified by MER, and the prediction remained after accounting for the depth of the upper border of the STN identified by MER. In addition, only the difference in depth between the HBP and the site of chronic stimulation significantly predicted the therapeutic efficacy of DBS with respect to contralateral bradykinesia-rigidity hemibody scores. Conclusion: Our results confirm the predictive value of the DBS electrode recorded LFP and strengthen the argument that LFP patterns may help aid DBS targeting and programming.